4x-5=2+3x-9

Simple and best practice solution for 4x-5=2+3x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-5=2+3x-9 equation:


Simplifying
4x + -5 = 2 + 3x + -9

Reorder the terms:
-5 + 4x = 2 + 3x + -9

Reorder the terms:
-5 + 4x = 2 + -9 + 3x

Combine like terms: 2 + -9 = -7
-5 + 4x = -7 + 3x

Solving
-5 + 4x = -7 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-5 + 4x + -3x = -7 + 3x + -3x

Combine like terms: 4x + -3x = 1x
-5 + 1x = -7 + 3x + -3x

Combine like terms: 3x + -3x = 0
-5 + 1x = -7 + 0
-5 + 1x = -7

Add '5' to each side of the equation.
-5 + 5 + 1x = -7 + 5

Combine like terms: -5 + 5 = 0
0 + 1x = -7 + 5
1x = -7 + 5

Combine like terms: -7 + 5 = -2
1x = -2

Divide each side by '1'.
x = -2

Simplifying
x = -2

See similar equations:

| 84/h=6 | | 3/10+7/20 | | 3/16+1/2 | | 10-(2y-6)y= | | -81=g*-9 | | 3q-5/8=0 | | X^4+10x^2+25=49 | | 2.5x=10-1.4x | | X/7=175 | | 7(17/18)-9/10 | | N^2+14n-32=0 | | 5/10=(x+1)/2 | | -4x+(-7x)-(-2x)= | | 6p+6=-3+3p | | x(x-5)=x^2+7x+7 | | 6v+3(-4+v)=-84 | | (5x^2-6x^3+11)+(9x^3+3x+7x^4)= | | 717/18-8/10 | | C=1001X+15236 | | y=140x+300 | | 4x-12+6=14+2x | | |k|-6-1 | | 6p+6=-e | | 8=-2y-6 | | 3/10-1/5 | | 85/9-49/6 | | 12t-5=0 | | 0.5q=.25 | | -7x-20=-48 | | 8-52/7 | | 4x+7=1+4x+6 | | 44=12+b+7b |

Equations solver categories